PEG-tethered guanosine acetal conjugates for the enzymatic synthesis of modified RNA - Wahl, Florentine; Jäschke, Andres (Biochemical and biophysical research communications, 2012)
A short and efficient synthetic route to guanosine monophosphate conjugates connected to a protected aldehyde group via a flexible polydisperse polyethylene glycol linker is described. These conjugates are enzymatically incorporated into RNA transcripts with 52% yield. The resulting aldehyde-modified RNA gave full conversion in the reaction with biotin hydrazide, demonstrating the utility of the method.
Available online 2 January 2012
Gesehen am 28.06.2018